External financing and firm growth: Evidence from Micro, Small, and Medium Enterprises in Iran - Iman Cheratian; Saleh Goltabar; Hassan Gholipour Fereidouni; Mohammad Reza Farzanegan (Philipps-University Marburg, School of Business and Economics, 2023)
This study examines the relationship between access to finance and growth in sales for Micro, Small, and Medium Enterprises (MSMEs) in Iran. Using data from 486 firms in five provinces, our findings indicate that external financing positively impacts sales growth for MSMEs. The results suggest that financing for research and development expenditures, production diversification, new employment and advertising can significantly contribute to increased sales growth. We also find that spending on intellectual property, labor training and land and building acquisition have a negative moderating effect on the relationship between finance and sales growth.
Keywords: G21; G32; G38; O16; O53; 330; Finance-sale growth nexus; Micro; Small; and Medium Enterprises (MSMEs); Iranian economy; External financing